Monte-Carlo Credit Assessment in Securities Financing and Lending - Shi, Yan; Tang, Chong (Transactions on Economics, Business and Management Research, 2024)
This paper presents a Monte-Carlo simulation-based model for credit assessment in the securities financing and lending sector, aimed at improving the precision of credit evaluations amidst market uncertainties. The methodology involves a stochastic approach to account for the complex variables affecting client creditworthiness. The model’s construction, parameter selection, and mathematical underpinnings are detailed, followed by an empirical analysis using historical transaction data. The findings underscore the model’s predictive capabilities and its comparative performance against existing models. The paper concludes with implications for risk management and directions for future research, emphasizing the model’s potential for further refinement.